Pembelajaran berbasis projek dan penerapanya dalam meningkatkan kreatifitas siswa-siswi madrasah ibtida’iyah - putri, manda reva (Maliki Interdisciplinary Journal, 2026)
This study aims to determine whether the Project-Based Learning (PjBL) model is effective in improving the creativity of third-grade students at MI Mambaul Ulum Kaliacar in learning the Qur’an and Hadith. The study used a qualitative approach with the Classroom Action Research (CAR) method. Data were collected through observation, interviews, questionnaires, and documentation. Then, the data were analyzed quantitatively and qualitatively descriptively. The results showed that the implementation of PjBL successfully improved aspects of creativity such as fluency, uniqueness, and the ability to elaborate ideas. Creativity scores increased from 65% to 85% from the first cycle to the second cycle. Student engagement also increased from 70% to 85%, and the student satisfaction level reached 80%. Challenges faced such as limited time and differences in students’ initial abilities can be overcome with the help of more active and intensive teachers. This study shows that PjBL is effective in increasing students’ creativity and motivation to learn actively and meaningfully. This model is also able to create a more interactive and enjoyable learning atmosphere. Thus, PjBL is an appropriate learning model to improve students’ abilities in the fields of religion and science as a whole.